2019
DOI: 10.21037/tau.2019.03.09
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s gangrene: a modern analysis of predictors of outcomes

Abstract: Background: Fournier's gangrene (FG) is a rapidly progressing necrotizing fasciitis that carries a significant morbidity and mortality. The present study sought to identify the predisposing factors related to FG and validate the Fournier's Gangrene Severity Index (FGSI) score as a prognostic tool in the care of the Fournier's patient.Methods: Medstar Washington Hospital Center records were searched from January 2003 to February 2015 for all patients with a diagnosis code of FG, n=42. Epidemiologic data was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 23 publications
0
29
1
9
Order By: Relevance
“…It has been reported that there was a 75% probability of death in patients with a score of FGSI greater than 9 [6]. The benefit of the FGSI has been also shown by other studies [3,8,9,11,12,16,20]. However, some researchers showed that there was no significant association between FGSI and mortality [10,13].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It has been reported that there was a 75% probability of death in patients with a score of FGSI greater than 9 [6]. The benefit of the FGSI has been also shown by other studies [3,8,9,11,12,16,20]. However, some researchers showed that there was no significant association between FGSI and mortality [10,13].…”
Section: Discussionmentioning
confidence: 82%
“…In most of the previously published studies, the presence of DM in patients with FG has been shown as one of the major prognostic factors for morbidity and mortality [1,16,[20][21][22]. Nevertheless, some researchers did not report significant associations between DM and FG [2,3,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most studied comorbid factors are diabetes mellitus, history of alcohol, age, the bacteria that causes Fournier's gangrene and others. 5 This retrospective study examined the factors that exist in patients towards the successful closure of defects in Fournier's gangrene. In this study, various factors such as age, smoking status, alcohol history, diabetes mellitus, hypertension, and bacteria that cause infections to successfully close defects in Fournier's gangrene were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…1). Uludag Fournier's Gangrene severity Index (UFGsI) [9,10]. Some authors apply adjuvant hyperbaric oxygen therapy or vacuum assisted therapy [11].…”
Section: Case Presentationmentioning
confidence: 99%